1990
DOI: 10.1007/bf00010752
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of 15N-ammonium in forest soils

Abstract: To determine the fate of atmospheric ammonium in forest soils, one calcareous and two acid forest soils were incubated with ~SN ammonium. In the calcareous soil about 65% of the applied ~5N-ammonium was recovered as nitrate after 98 days of incubation, whereas in the acid soils less than 10% of the 15N-ammonium was converted to nitrate. In all soils a large proportion of the ~5N was incorporated in organic nitrogen compounds. This incorporation limits the use of 15N tracers for the elucidation of the fate of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Organic nitrogen is the predominant form of N in most temperate forest soils [30,31]. In one calcareous and two acid forest soils the proportion of organic N was more than 95% of the total [30].…”
Section: Forms Of Organic Nitrogen Available In Forest Soilsmentioning
confidence: 99%
“…Organic nitrogen is the predominant form of N in most temperate forest soils [30,31]. In one calcareous and two acid forest soils the proportion of organic N was more than 95% of the total [30].…”
Section: Forms Of Organic Nitrogen Available In Forest Soilsmentioning
confidence: 99%
“…Organic nitrogen is the predominant form of N in most temperate forest soils [30, 31]. In one calcareous and two acid forest soils the proportion of organic N was more than 95% of the total [30].…”
Section: Extracellular Degradation Of Organic Nitrogen Compoundsmentioning
confidence: 99%
“…This shift in approach to the study of nitrogen mineralization has been made possible by technological advances (faster colorimetric analysis of inorganic-N by Flow Injection Analysis and the ready availability and relatively cheap price of isotopes and mass spectrometers) and has benefited greatly from new techniques (for example, fumigation methods for microbial biomass, carbon, nitrogen and phosphorus; see review by Parkinson & Coleman, 1991 For many years it was thought that nitrification was negligible in soils of low pH; there are now numerous reports of nitrification in forest soils of pH less than 5 (e.g. Williams, 1972;Remade, 1977;Van Miegrot & Cole, 1985;Adams & Attiwill, 19866;Van Breemen, De Visser & Van Grinsven 1986;Becquer et al, 1990;Stams et al, 1990). Together with the observations of nitrification in acidic heathland, grassland and woodland soils, these results have prompted studies which have demonstrated :…”
Section: Phosphorus Cycling and Availability In Forest Soilsmentioning
confidence: 99%
“…(i) That heterotrophic nitrification is a significant process (Schimel, Firestone & Killham, 1984, Adams 1986Stroo, Klein & Alexander, 1986 Stams et al, 1990;Stams et al, 1991).…”
Section: Phosphorus Cycling and Availability In Forest Soilsmentioning
confidence: 99%